Building Bureaucratic Capacity for Improved Public Service Quality in Makassar City, Indonesia - Jamal Qadar; Besse Herlina; Zulfachri Zulfachri; Sofyan Marzuki (Government & Resilience, 2026)
The shift toward regional autonomy in Indonesia aims to bring public services closer to the community, with the expectation of improving service quality and ensuring that the benefits are felt by all stakeholders. However, local governments continue to face significant challenges in meeting the growing demand for high-quality public services, especially in crucial sectors such as clean water, health, population management, and licensing. This research evaluates the bureaucratic capacity of Makassar City, South Sulawesi, from 2020 to 2024, using a qualitative approach and descriptive analysis. Data was gathered through interviews with 12 key informants and secondary sources, including official documentation. The analysis reveals that the public service performance in Makassar does not meet community expectations, mainly due to limitations in the local government's bureaucratic capacity. These limitations include insufficient personal, organizational, and system capacities, weak political will, and low community engagement. The study concludes that improving bureaucratic capacity is essential for enhancing public service delivery. To address these challenges, the study proposes four key policy recommendations: 1) Developing a strategic plan for bureaucratic capacity building, 2) Innovating government policies to better meet community needs, 3) Implementing participatory reforms, and 4) Investing in information technology to enhance governance. The main contribution of this research is providing a deeper understanding of the role of bureaucratic capacity in improving quality of public service and developing policies that are more responsive to the needs of the community.